Mapping geomorphology changes of spit at Kuala Terengganu estuary using multi-temporal synthetic aperture radar (SAR) data - 252365 Zurina Sabu; Maged Mahmoud Marghany (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2007